Penatalaksanaan Fisioterapi pada Tennis Elbow Sinistra dengan Ultrasound dan Terapi Latihan - Mayyaza Min Azkia; Kuswardani Kuswardani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Tennis elbow, or lateral epicondylitis, is an inflammatory condition of the lateral epicondyle commonly caused by repetitive overuse of the forearm extensor muscles. It is characterized by pain, limited joint range of motion, decreased muscle strength, and reduced functional capacity. Physiotherapy interventions, particularly ultrasound and exercise therapy, have been widely applied to reduce pain and restore functional performance. This study employed a case study design involving a 42-year-old female patient diagnosed with left-sided tennis elbow. The intervention was conducted over four therapy sessions. The modalities consisted of ultrasound, providing thermal and micromassage effects to reduce pain, combined with exercise therapy, including passive stretching to increase soft tissue flexibility and eccentric exercise to improve tendon strength and function. After four sessions, the patient showed significant improvement, including reduced pain during movement and palpation, increased joint range of motion in elbow flexion-extension, forearm pronation-supination, and wrist dorsiflexion-palmarflexion. Muscle strength, particularly in the extensors, pronators, supinators, and wrist dorsiflexors, also improved. Functional activity, measured using the PRTEE scale, demonstrated notable enhancement from mild disability to better functional independence. The combination of ultrasound, passive stretching, and eccentric exercise is effective in reducing pain, enhancing range of motion, strengthening muscles, and improving functional ability in patients with left-sided tennis elbow.